간호대학생의 간호현장 내 무례함 대처 유형 - 주민선(Min Sun Chu); 박창승(Chang Seung Park); 황윤영(Yoon Young Hwang) (다문화건강학회지, 2021)
This study was done to identify a typology of coping styles toward incivility in clinical sites among nursing students using Q methodology for providing data of nursing education program. Initially, 85 Q statements were extracted, and 36 statements were generated as the final Q sample. Considering the various clinical practice experience, 42 senior nursing students were selected by convenience sampling. Q sorting yielded in each case a systematic forced distribution of 36 Q samples ordered on a scale of 1–9. The collected data were analyzed using the PC-QUANL program by performing principle component analysis. The factor analyses revealed four types of coping style that together for 55.43% of variance: Type 1 (37.30%), Type 2 (9.02%), Type 3 (5.35%), and Type 4 (3.76%). The revealed four types of nursing students coping styles toward incivility in clinical sites: Type Ⅰ is "Active conversion type", type Ⅱ is "Passive evasion type", type Ⅲ is "Resignation endurance type", and type Ⅳ is "Rational immersion type." Further study needs to develop and apply effective nursing education program based on differentiated coping style types toward incivility in clinical sites among nursing students. In addition, it is necessary to establish a policy to create a sound clinical practice environment in order to reduce the incivility experienced by nursing students in clinical sites. KCI Citation Count: 1